PHYSICAL-MECHANICAL PROPERTIES OF LIME AND SAND MORTARS WITH ADDITION OF BURNED CLAY POZZOLANA, FOR RESTORATION OF BUILDINGS CAJAMARCA, PERU - Huamán Moreno, Sara Elizabeth; Mosqueira Moreno, Miguel Angel; Mosqueira Ramírez, Hermes Roberto; Huamán Sangay, Sergio Manuel (LACCEI, 2024)
In this study, the impact of the incorporation of fired clay pozzolana on the physical-mechanical properties of mortars composed of lime and sand was investigated. The research was carried out in the context of Cajamarca, a place that houses a valuable cultural heritage, especially churches built with lithic structures of incalculable historical value. The central objective of this work focuses on the intrinsic connection between the addition of fired clay pozzolana and the preservation and restoration of these historical stone monuments, which are restored with lime, sand and fired clay mortars, but without having a dosage that allows greater resistance. That is why tests were carried out with four mortar dosages, including the 1:3 control dosage of lime and sand. The results indicated that the most promising combination in terms of physical-mechanical properties was that of lime, sand and pozzolana in a 1:3:2 ratio (D4) as it demonstrated notable improvements in several properties of the mortars; The mechanical resistance to compression experienced a significant increase of 83.66%, with an average of 2.81 kg/cm2 compared to 1.53 kg/cm2 with the lime-sand mortar in a 1:3 ratio (D1). Likewise, tensile adhesion improved by 76.92%, reaching an average of 0.23 kg/cm2 for D4 compared to 0.13 kg/cm2 for D1. The apparent density also increased by 1.65% with the D4 dosage, evidencing greater compactness of the mortar. Finally, absorption decreased notably in D4, reaching 61.44% less than in D1, indicating lower porosity and better water resistance. These findings suggest that the addition of fired clay pozzolana may be an effective strategy to improve the properties of lime and sand mortars, especially in the context of historical heritage conservation in Cajamarca, Peru.